2011
DOI: 10.1007/s00127-011-0411-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the ‘hikikomori’ syndrome of social withdrawal exist outside Japan? A preliminary international investigation

Abstract: Purpose To explore whether the ‘hikikomori’ syndrome (social withdrawal) described in Japan exists in other countries, and if so, how patients with the syndrome are diagnosed and treated. Methods Two hikikomori case vignettes were sent to psychiatrists in Australia, Bangladesh, India, Iran, Japan, Korea, Taiwan, Thailand and the USA. Participants rated the syndrome's prevalence in their country, etiology, diagnosis, suicide risk, and treatment. Results Out of 247 responses to the questionnaire (123 from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
197
1
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(220 citation statements)
references
References 39 publications
9
197
1
13
Order By: Relevance
“…All of these difficulties could make war-traumatized children more challenging to manage for their parents, who, in turn, may apply more violent and coercive parenting strategies. Consistent with this hypothesis, a recent study with Tamil families in post-war Sri Lanka found that children's exposure to mass trauma and child psychopathology were the main predictors of children's self-reported victimization in their families, even after controlling for parental trauma and parental mental health 5 .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…All of these difficulties could make war-traumatized children more challenging to manage for their parents, who, in turn, may apply more violent and coercive parenting strategies. Consistent with this hypothesis, a recent study with Tamil families in post-war Sri Lanka found that children's exposure to mass trauma and child psychopathology were the main predictors of children's self-reported victimization in their families, even after controlling for parental trauma and parental mental health 5 .…”
mentioning
confidence: 75%
“…The Japanese sociocultural background has been traditionally permeated by "amae" (accepting overdependent behaviors) and shame, which may underlie the culture-bound syndrome called Taijin Kyofusho (a severe form of social phobia) as well as hikikomori 5,6 . Parent-child relationships in Japan have long been considered less oedipal than in Western societies and marked by an absent father and an extremely prolonged and close bond to the mother, which may result in difficulty to become independent 7 .…”
Section: Claudia Catanimentioning
confidence: 99%
“…Because of prolonged social withdrawal, patients with hikikomori syndrome may develop vitamin D deficiency due to inadequate exposure to sunlight. Nonetheless, hypocalcaemia and/or vitamin D deficiency has not previously been reported in hikikomori syndrome [1,2] and may have been overlooked. In fact, Chvostek's and/or Trousseau's signs were both negative in this case, and hypocalcaemia was found incidentally during the general laboratory investigation.…”
Section: Discussionmentioning
confidence: 95%
“…There are almost 1 million hikikomori in Japan between the ages of 20 and 40. Hikikomori syndrome [1,2] is regarded as a mental or psychiatric disorder and most probably for this reason, metabolic abnormality, in particular hypocalcaemia, associated with this condition has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…The hikikomori syndrome appears to be especially common in urban settings. 10 While psychiatrists from diverse cultures recognise the hikikomori syndrome, management differs and there is little agreement about the underlying aetiology. Hikikomorilike phenomena are 'somewhat accepted' in Japanese society and psychiatrists tend to suggest psychotherapy, especially for teenage patients.…”
Section: Two-way Trafficmentioning
confidence: 99%